2016
DOI: 10.1002/yea.3211
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and genomic characterization of a yeast model for Ogden syndrome

Abstract: Naa10 is an Nα‐terminal acetyltransferase that, in a complex with its auxiliary subunit Naa15, co‐translationally acetylates the α‐amino group of newly synthetized proteins as they emerge from the ribosome. Roughly 40–50% of the human proteome is acetylated by Naa10, rendering this an enzyme one of the most broad substrate ranges known. Recently, we reported an X‐linked disorder of infancy, Ogden syndrome, in two families harbouring a c.109 T > C (p.Ser37Pro) variant in NAA10. In the present study we performed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 86 publications
1
13
0
Order By: Relevance
“…Third, Nt acetylation has been connected to protein folding and stability because it reduces the Nt charge and thereby can stabilize Nt a helices of proteins, such as mitochondrial chaperonin 10 (Cpn10) (Jarvis et al, 1995;Ryan et al, 1995), tropomyosin (Greenfield et al, 1994), and a-synuclein (Bartels et al, 2014;Dikiy and Eliezer, 2014). Finally, a number of publications link Nt acetylation to protein degradation in yeast (Pezza et al, 2009;Zattas et al, 2013;Holmes et al, 2014;Dö rfel et al, 2017;Oh et al, 2017). There, acetylated N termini form an N-degron that targets proteins via the Ac/N-end rule pathway for ubiquitination by E3 ubiquitin ligases, including Not4 and Doa10, followed by proteasomal degradation (Hwang et al, 2010;Shemorry et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Third, Nt acetylation has been connected to protein folding and stability because it reduces the Nt charge and thereby can stabilize Nt a helices of proteins, such as mitochondrial chaperonin 10 (Cpn10) (Jarvis et al, 1995;Ryan et al, 1995), tropomyosin (Greenfield et al, 1994), and a-synuclein (Bartels et al, 2014;Dikiy and Eliezer, 2014). Finally, a number of publications link Nt acetylation to protein degradation in yeast (Pezza et al, 2009;Zattas et al, 2013;Holmes et al, 2014;Dö rfel et al, 2017;Oh et al, 2017). There, acetylated N termini form an N-degron that targets proteins via the Ac/N-end rule pathway for ubiquitination by E3 ubiquitin ligases, including Not4 and Doa10, followed by proteasomal degradation (Hwang et al, 2010;Shemorry et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Among these, the X-linked Ogden syndrome (OS) [25,26] shows the most severe pathological features such as infant lethality and has reduced NatA catalytic activity. In a Saccharomyces cerevisiae model for the Naa10 Ser37Pro mutant, the mutation impairs NatA complex formation and leads to a reduction in NatA catalytic activity and functionality [27,28]. Further, OS patient-derived cells have impaired amino-terminal acetylation in vivo of some NatA substrates [25].…”
Section: Introductionmentioning
confidence: 99%
“…This reduction most likely occurs because the variant transcript is targeted for degradation via the nonsense-mediated decay (NMD) pathway. 20 We further explored the functional effects for two of the other LGDs in a yeast assay in which the human NatA complex can functionally replace yeast NatA, as shown by complementation of growth phenotypes 21,22 and partial rescue of the NatA-specific Nt-acetylome. 23 Mutant NAA15 (p.Thr55Hisfs*2 [c.163delA] from family 2 and p.Lys305* [c.913A>T] from family 18) failed to rescue the temperature-sensitive growth phenotype of yNatAD (Figure 4A and Tables S7, S8, and S9), suggesting that the two variants lead to reduced or abolished NatA activity, at least as assessed in this heterologous system.…”
mentioning
confidence: 99%
“…27 Most studies have reported that missense mutations in NAA10 decrease the enzymatic function of NAA10 and/or decrease its binding to NAA15. 21,22,27,35,39,40 In total, the presentations involving NAA10 and NAA15 appear to have phenotypic overlap but variability, and as such should be referred to more broadly as ''NAA10related syndrome'' and ''NAA15-related syndrome.'' The extensive phenotypic variability is most likely related to genetic background differences and also to the spatial and temporal tissue-specific acetylation of a few N-terminal acetylation substrates by the NatA complex, although there are also suggested N-terminal acetylation (NTA)-independent functions for NAA10.…”
mentioning
confidence: 99%